Peculiar Portrayals: Mormons on the Page, stage, and Screen - Austin, Michael (Utah State University, University Libraries, 2010)
Center and periphery: Mormons and American culture in Tony Kushner's Angels in America / Cristine Hutchison-Jones -- Four consenting adults in the privacy of their own suburb: Big love and the cultural significance of Mormon polygamy / Michael Austin -- Teaching under the banner of heaven: testing the limits of tolerance in America / Kevin Kolkmeyer -- Avenging angels: the Nephi archetype and blood atonement in Neil LaBute, Brian Evenson, and Levi Peterson, and the making of the Mormon American writer / J. Aaron Sanders -- Elders on the big screen: film and the globalized circulation of Mormon missionary images / John-Charles Duffy -- "I constructed in my mind a vast, panoramic picture": the miracle life of Edgar Mint and postmodern, postdenominational Mormonism / Mark T. Decker -- Jane Austen in Mollywood: mainstreaming Mormonism in Andrew Black's Pride & prejudice / Juliette Wells -- Reality corrupts, reality television corrupts absolutely / Karen D. Austin